GE_GERICHTE P/16015/2011 vom 27. April 2016 - GE Cour de justice (2016)
RIXE; DÉFENSE; AGRESSION; BAGARRE; TORT MORAL; MOTIVATION DE LA DEMANDE; DÉPENS; FRAIS DE LA PROCÉDURE | CP.133.1; CP.133.2; CP.134; CPP.429; CO.41; CO.46; CO.47